Extracellular Signal-Regulated Kinase Activity Is Sustained Early during Human Cytomegalovirus Infection - Rodems, Steven M. (American Society for Microbiology, 1998)
Expression of many early viral genes during human cytomegalovirus (HCMV) infection is dependent on cellular transcription factors. Several immediate-early and early viral promoters contain DNA binding sites for cellular factors such as CREB, AP-1, serum response factor, and Elk-1, and these transcription factors can be activated by phosphorylation via the cellular mitogen-activated protein kinase (MAPK) signal transduction cascade. To determine if the extracellular signal-regulated MAPKs, ERK1 and ERK2, play a role in transcription factor activation during infection, we tested for ERK activity during viral infection. We found that HCMV infection resulted in the maintenance of previously activated ERK1 and ERK2 by a mechanism which appears to involve the inhibition of a cellular phosphatase activity. ERK phosphorylation and activity were sustained for at least 8 h after infection, whereas in mock-infected cells, ERK activity steadily declined by 1 h postinfection. The activity of at least one cellular substrate of the ERKs, the protein kinase RSK1, was also maintained during this period. UV inactivation experiments suggested that viral gene expression was required for sustained ERK activity. In turn, activation of the ERKs appeared to be important for viral gene expression, as evidenced by the observed decrease in the transcriptional activity of the HCMV UL112-113 promoter during infection in the presence of the MEK inhibitor PD98059. These data suggest that HCMV utilizes cellular signal transduction pathways to activate viral or cellular transcription factors involved in the control of early viral gene expression and DNA replication.